EXISTENCE OF ALKHAIRAAT ON CENTRAL SULAWESI POLITICS Case Study: Opportunity of Alkhairaat after the local election 2015 - Nurhidayat Mohammad Ishak (IPEM 16 UMY 258, 2016)
This research is trying to findout how the existence of Alkhairaat on politics in Central Sulawesi. Alkhairaat is one of the great organizations in Central Sulawesi even in the eastern part of Indonesia. Alkhairaat as a great organization is certainly has a great influence also to Central Sulawesi community. Concurrent local election 2015 in Central Sulawesi, Alkhairaat discovered to openly support one candidate Governor of Central Sulawesi.Therefore, focus of this study is looking for how the involvement of Alkhairaat directly on politics in Central Sulawesi, especially at a time when local election 2015. Find out what the reason Alkhairaat involved in politics, by supporting one of the Central Sulawesi Governor candidates. Then analyze how opportunities gotten by Alkhairaat after local election2015. Keywords :Alkahiraat, Involved, Local Election, Exsistence, Opportunity